2008
DOI: 10.1021/ja806344y
|View full text |Cite
|
Sign up to set email alerts
|

2H Solid-State NMR of Ruthenium Complexes

Abstract: The (2)H solid-state NMR spectra of the transition metal complexes Tp*RuD(THT)(2) (1a), Tp*RuD(D(2))(THT) (1b), Tp*RuD(D(2))(2) (1c), Cp*RuD(3)(PPh(3)) (2) and RuD(2)(eta(2)-D(2))(2)(PCy(3))(2) (3) have been measured in a wide temperature range. These compounds were chosen as potential model systems for hydrogen surface species in Ru-nanoparticles. The deuterium quadrupolar coupling constants Q(cc) and asymmetry parameters were extracted by (2)H NMR line-shape analysis. The Q(cc) values of the deuterons bound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…Recently, some of the authors have proposed the foundation of this work, with molecular density functional theory (DFT) calculations of quadrupole coupling constants Q cc and the asymmetry parameter η Q , (see the Supporting Information for definitions) of deuteron in ruthenium complexes6 directly comparable with the experimental data 1g. There is no doubt now that joint theoretical/experimental studies are a very powerful approach to complete the partial understanding of deuteron solid‐state NMR spectra.…”
Section: Quadrupole Coupling Constants (Qcc) In Khz and The Asymmetrymentioning
confidence: 70%
“…Recently, some of the authors have proposed the foundation of this work, with molecular density functional theory (DFT) calculations of quadrupole coupling constants Q cc and the asymmetry parameter η Q , (see the Supporting Information for definitions) of deuteron in ruthenium complexes6 directly comparable with the experimental data 1g. There is no doubt now that joint theoretical/experimental studies are a very powerful approach to complete the partial understanding of deuteron solid‐state NMR spectra.…”
Section: Quadrupole Coupling Constants (Qcc) In Khz and The Asymmetrymentioning
confidence: 70%
“…If in solution, the hydrides and the dihydrogen ligands are in fast exchange, extensive knowledge has been gained regarding the coordination modes of the hydrogen atoms around the coordination sphere of the metal in the solid state. The most recent achievements are the solid-state NMR data for 1 40 and the neutron structure for 2. 32 With six hydrogen atoms around the ruthenium, one can expect evolution of 3 equiv of dihydrogen, but we have shown that the phosphine ligands are also a potential source of dihydrogen evolution through C-H activation.…”
Section: Reversible Hydrogen Releasementioning
confidence: 99%
“…For example, the influence of amine and phosphine ligands on the size and shape control of Pd and Ru nanoparticles, [39][40][41] the influence of a diphosphine on the dynamics of CO molecules and their oxidation in comparison with the polymer PVP 42 or the coordination of NHC-carbenes on the a Institute of Physical Chemistry, Technical University Darmstadt, surface of RuNPs and their effect on the hydrogenation of styrene or other arenes were determined. 43,44 Inspired by previous experimental and theoretical solid-state NMR investigations of deuterium/hydrogen in Ru complexes and clusters, [45][46][47][48][49][50] surface investigations by 2 H solid-state NMR techniques allowed us to obtain useful information on the complex phenomena taking place on the surface of the particles. [51][52][53][54][55] Detailed overviews on these investigations are given in two recent reviews.…”
Section: Introductionmentioning
confidence: 99%